Variability of Martian Turbopause Altitudes. Issue 11 (5th November 2018) - Slipski, M.; Jakosky, B. M.; Benna, M.; Elrod, M.; Mahaffy, P.; Kass, D.; Stone, S.; Yelle, R.
Abstract: The turbopause and homopause represent the transition from strong turbulence and mixing in the middle atmosphere to a molecular‐diffusion‐dominated region in the upper atmosphere. We use neutral densities measured by the Neutral Gas and Ion Mass Spectrometer on the Mars Atmospheric and Volatile EvolutioN spacecraft from February 2015 to October 2016 to investigate the temperature structure and fluctuations of the Martian upper atmosphere. We compare those with temperature measurements of the lower atmosphere from the Mars Reconnaissance Orbiter's Mars Climate Sounder. At the lowest Mars Atmospheric and Volatile EvolutioN altitudes we often observe a statically stable region where waves propagate freely. In contrast, regions from about 20 km up to at least 70 km are reduced in stability where waves are expected to dissipate readily due to breaking/saturation. We derive homopause altitudes from Neutral Gas and Ion Mass Spectrometer N2 and Ar densities and find that it varies between 60 and 140 km. From the standard deviations in monthly averaged temperature profiles, we determine the wave turbopause altitude where applicable and find that these altitudes agree with the homopause altitudes. We show that the homopause variability is driven by order of magnitude changes in CO2 densities, which drastically affect the altitude at which the eddy diffusion is equal to the molecular diffusion. These variations are observed as a function of local time, latitude, and season. That the turbopause/homopause does not track a fixed density level means that the eddy diffusion coefficient at the turbopause can vary significantly, suggesting differences in the dominant breaking waves and tidal modes. Plain Language Summary: The gases that make up a planet's atmosphere are mixed together efficiently near the surface. But in the uppermost part of the atmosphere, gases separate by mass—heavier ones are held closer to the planet, while lighter ones are more abundant higher up. Because turbulence is responsible for the mixing in the atmosphere, the altitude where this transition occurs is called the turbopause. That turbulence is thought to be generated by atmospheric waves that lose energy (somewhat like ocean waves breaking at shore). In this work, we use measurements of the upper atmosphere from Mars Atmosphere and Volatile Evolution Mission and of the lower atmosphere from Mars Reconnaissance Orbiter to study the turbopause region during a full Mars year. Similar to Earth's atmosphere, we find that below the turbopause wave breaking is strong (which produces turbulence), but above waves can move freely. We also show that the turbopause varies significantly depending on the season and location on the planet. At Mars, gases can escape from the top of the atmosphere, so the relative amounts of escape of different gases depends on the turbopause. Understanding this altitude and why it varies is important for interpreting how the atmosphere evolved. Key Points: Mars's turbopause is governed by the transition from strong wave dissipation and turbulence to weak dissipation and freely propagating waves We use lower and upper atmospheric temperature observations and N2 /Ar ratios to investigate the turbopause region over a full Mars year Mars's turbopause and homopause altitudes exhibit the same variations with local time, latitude, and season.